Effects of Titanium Dioxide Nanoparticles and Coenzyme Q10 on Testicular Ischemia-Reperfusion Injury: Role of the Mitochondrial Apoptosis Pathway: - Hashemi, Mehrdad; Masoumi, Masoumeh; Salehi, Mitra; Abdolhamid Angaji, Seyed (Galen Medical Journal, 2022)
Background: Testicular ischemia-reperfusion (I/R) injury is a urological emergency that can lead to male infertility. So far, no suitable treatment has been found for it. Therefore, in the present study, we investigate the therapeutic effects of concomitant administration of coenzyme Q10 (CoQ10) and titanium dioxide nanoparticles (TiO2-NPs) on testicular I/R damage in rats and the expressions of genes involved in mitochondrial apoptosis, miR-21, and circRNA0001518. Materials and Methods: In this study, after induction of testicular torsion/detorsion, CoQ10 and TiO2-NPs were administered to the rats for ten days. Then, sperm extracted from the epididymides were analyzed for concentration, viability, morphology, and motility. The amount of apoptosis in testicular cells was studied by flow cytometry. Also, the expressions of the Bax and Bcl-2 genes, as well as miR-21 and circRNA0001518 levels were evaluated. Results: Sperm parameters improved in the rats’ testicular that received CoQ10. Administration of TiO2-NPs to healthy rats increased apoptosis and the Bax/Bcl-2 expression ratio. However, its administration to testicular I/R rats alone or in combination with CoQ10 caused a decrease in apoptosis, the Bax/Bcl-2 expression ratio, and an increase in miR-21 and circRNA0001518 expressions. Conclusion: Overall, individual or joint administration of TiO2-NPs or CoQ10 can have therapeutic effects on testicular I/R by altering the expressions of genes in the mitochondrial apoptotic pathway and their regulatory elements.